A multi-omics study of the anti-cancer effect of a ferulic acid derivative FA-30. (10th August 2022) - Wang, Dongyao; Guo, Dandan; Tang, Yuxiao; Qi, Minyu; Fang, Jiahao; Zhang, Ying; Chai, Yifeng; Cao, Yan; Lv, Diya
Abstract : The active ingredients of Traditional Chinese Medicine are an important source of bioactive molecules and play an important role in the research and development of innovative drugs. Abstract : The active ingredients of Traditional Chinese Medicine are an important source of bioactive molecules and play an important role in the research and development of innovative drugs. FA-30, which is a derivative of natural product ferulic acid, inhibited cervical cancer cell proliferation and induced apoptosis as well. To understand the underlying mechanisms of FA-30, a complementary multi-omics study was conducted. Cysteine and methionine metabolism and aminoacyl-tRNA biosynthesis pathways were significantly changed both at the metabolic level and proteomic level. This may help us to get a better understanding of cervical cancer and FA-30 at the same time.